Polypharmacy in atrial fibrillation: A prospective analysis of mortality and ischemic stroke using the Clinical Practice Research Datalink - Natasha Slater; Simon White; Martin Frisher (Journal of Arrhythmia)
Abstract Background Observational studies of polypharmacy and the risk of death or stroke in individuals with atrial fibrillation (AF) have produced inconsistent findings. By using propensity score matching (PSM) and Cox regression, this study aimed to determine whether polypharmacy (five to nine medicines) in the 3 months following AF diagnosis, is associated with an increased risk of death or ischemic stroke, compared to non‐polypharmacy (one to four medicines). Methods A prospective cohort study using data from the Clinical Practice Research Datalink (2006–2019). Data from 23 629 individuals with AF were analyzed. Cox regression models were adjusted for age, gender, morbidities, obesity, alcohol, smoking, and wealth. In the PSM models, cases and controls with near identical health profiles were selected from the study pool. The risk of death and stroke were presented as hazard ratios (HRs) with 95% confidence intervals (CIs). Results 68.9% (n = 16 271) of the participants had polypharmacy. PSM showed that polypharmacy was associated with an increased risk of death during follow‐up (HR 1.32; 95% CI: 1.19–1.47, p < .01), but not ischemic stroke (HR 0.84; 95% CI: 0.69–1.02, p = .08). Conclusion Polypharmacy was associated with an increased risk of death during follow‐up, but not ischemic stroke, in individuals with AF. The effects of comorbidity and other confounding factors were reduced by using PSM. This study focused on the overall medication burden; however, further research is needed to identify which specific medications in polypharmacy regimens increase the risk of mortality in AF. These findings could inform prescribing practices in the future.